The Role of Parents and Coaches on Concentration and Confidence Levels During Matches for Novice Badminton Athletes in The City of Semarang - Jihan Nabilah; Sulaiman; Siti Baitul Mukarromah (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2025)
This study aims to analyze the role of parents and coaches towards novice athletes in Semarang City. The research method used in this study is a quantitative approach with a descriptive correlational method. The research subjects used in this study were novice athletes in Semarang City. Data collection by observation, questionnaire, and documentation. Quantitative data analysis consists of normality tests, and hypothesis testing using SPSS version 25 software. In the Parental Role variable, the minimum value obtained is 109.00, the maximum value is 163.00 and the average value is 123.92 with a standard deviation of 13.14. The results of the descriptive analysis test of the Role of the Coach variable showed that the minimum value was 100.00, the maximum value was 177.00 and the average was 123.45 with a standard deviation of 12.98. Furthermore, the results of descriptive analysis of the Concentration variable obtained a minimum value of 5.00, a maximum value of 26.00 and an average of 11.81 with a standard deviation of 5.18. The results of the descriptive analysis of the Self-Confidence variable showed a minimum value of 104.00, a maximum value of 163.00 and an average of 126.65 with a standard deviation of 13.61. There is a significant relationship between the role of parents and coaches on the concentration and self-confidence of athletes both partially and simultaneously.This research may still have limitations so that suggestions for future researchers can expand the variables to be studied.